Hadith #4170 - Sahih al-Bukhari - Wahab bin Kaisan (Sahih al-Bukhari)
Jabir bin `Abdullah said, “Allah’s Messenger (ﷺ) sent troops to the sea coast and appointed Abu ‘Ubaida bin Al-Jarrah as their commander, and they were 300 (men). We set out, and we had covered some distance on the way, when our journey food ran short. So Abu ‘Ubaida ordered that all the food present with the troops be collected, and it was collected. Our journey food was dates, and Abu Ubaida kept on giving us our daily ration from it little by little (piecemeal) till it decreased to
Grade: Sahih